Malocclusion and socioeconomic indicators in primary dentition - Raulison Vieira de Sousa; Ana Karla de Almeida Pinto-Monteiro; Carolina Castro Martins; Ana Flávia Granville-Garcia; Saul Martins Paiva (Sociedade Brasileira de Pesquisa Odontológica, 2014)
The aim of the present study was to determine the prevalence of malocclusion and associations with socioeconomic indicators among preschoolers. A cross-sectional study was conducted with 732 children 3 to 5 years of age in the city of Campina Grande, Brazil. Three dentists underwent a calibration exercise (K = 0.85-0.90) and diagnosed malocclusion based on the criteria proposed by Foster & Hamilton and Grabowski et al. Parents/guardians answered a questionnaire addressing sociodemographic aspects. Data analysis involved descriptive statistics and bivariate Poisson regression (PR; α = 5%). The prevalence of malocclusion was 62.4%. The most frequent types were increased overjet (42.6%), anterior open bite (21%) and deep overbite (19.3%). An association was found between malocclusion and age: the prevalence of malocclusion was greater among younger children, with the highest prevalence among 3-year-olds (PR = 1.116; 95%CI = 1.049-1.187). The prevalence of malocclusion was high. Mother's schooling and household income were not associated with malocclusion. Socioeconomic factors were also not associated with the occurrence of malocclusion.